Implementing community participation via interdisciplinary teams in primary care: An Irish case study in practice. (16th May 2018) - Tierney, Edel; McEvoy, Rachel; Hannigan, Ailish; MacFarlane, Anne E.
Abstract: Background: Community participation in primary care is enshrined in international and Irish health policy. However, there is a lack of evidence about how stakeholders work collectively to implement community participation within interdisciplinary teams; community perspectives are rarely captured, and a theoretical underpinning for implementation of community participation in primary care is absent. Objective: To conduct a theoretically informed, multiperspectival empirical analysis of the implementation of community participation via primary care teams (PCTs) in Ireland. Methods/Design/Participants: Participatory learning and action (PLA) focus groups and interviews were held with 39 participants across four case study sites within a nationally funded programme designed to enable disadvantaged communities to participate in primary care. Normalization process theory (NPT) informed data generation and analysis of how diverse stakeholder groups worked together to implement community participation via PCTs. Results: The various stakeholders had a shared understanding of the value of community participation on PCTs. Motivations to get involved in this work varied, but were strong overall. Challenges to enacting community participation on PCTs included problems with the functioning of PCTs and a lack of clarity and confidence in the role of community representatives at PCT meetings. Informal appraisals were positive, but formal appraisal was limited. Discussion and Conclusion: The implementation and sustainability of community participation on PCTs in Ireland will be limited unless (i) the functioning of PCTs is strong, (ii) there is increased confidence and clarity on community representatives' roles among all health‐care professionals, and (iii) more sophisticated methods for formal appraisal are used.